PENGEMBANGAN MULTIMEDIA INTERAKTIF MATA DIKLAT MEMPERBAIKI MOTOR LISTRIK GUNA PENINGKATAN HASIL BELAJAR: (Development of Interactive Multimedia Course On Improving the Electric Motors For Improvement of Learning Outcomes) - Oriza Candra; Fivia Eliza; Syaiful Islami; Yosri Alisman (Perspektif Pendidikan dan Keguruan, 2019)
The purpose of this article is to improve the learning outcomes of students using interactive multimedia in the eyes of training to improve electric motors in SMK 1 Tanjung Raya. This type of research is a quasi-experimental design with a pretest-posttest one group. The subjects of this study were students of class XII TITL of SMK 1 Tanjung Raya who were enrolled in the 2013/2014 school year consisting of 29 students. Data collection in this study used a test of learning outcomes (posttest) in the form of objective questions as many as 20 items. Before the test questions were used then a test was conducted to determine the validity, reliability, level of difficulty of the questions and the different power of the questions. The data obtained were analyzed using the Gain Score. The results obtained indicate that there is an increase in student learning outcomes that can be seen from the results of the pretest and posttest values, the average value of pretest before using interactive multimedia is 64.48 and the average posttest value after using interactive multimedia is 75.07. So it was concluded that the use of interactive multimedia learning media can improve student learning outcomes in the eyes of training to improve the electric motor.